The Uniqueness of avifauna on islands in some lakes in Hanoi city - Nguyen Lan Hung, Son; Le, Thi Thu Hien; Vuong, Thu Phuong (Hue University Journal of Science: Natural Science, 2025)
Hanoi is a city characterized by many lakes and rivers. Some lakes have small islands separated from the shore or have bridges across them. The islands are unique ecological niches that contribute to maintaining biodiversity for the city. This is the habitat, shelter, feeding and nesting place of many species of birds. Research on the island avifauna in 4 lakes of Hanoi city in 2024-2025 recorded 63 bird species belonging to 10 orders, 28 families, 41 genera. Among them, there are 4 bird species that were listed in Decree 84/2021/ND-CP. The Ardeidae and Muscicapidae (7 species, Rdi = 11.11) being the most diverse families. There is one species that colonial nesting, the Chinese Pond-heron. Most of the species are resident birds (43 species, accounting for 68% of total species), the rest are winter visitor and passage migrant species. The area of ​​the island, the structure of the vegetation on the island, the separation of the island from the shore, the impact of human activities on the island or around the island are factors affecting the diversity of bird species on the island. Islands on lakes play an important role in maintaining the diversity and abundance of bird species in the city.